DESAIN DAN IMPLEMENTASI SECOND ORDER GENERALIZED INTEGRATOR-PHASE LOCKED LOOP (SOGI-PLL) UNTUK TEGANGAN SATU FASA MENGGUNAKAN DSPIC30F4011 DENGAN KONTROL PROPORTIONAL INTEGRAL - Purwanto, Aji; Setiawan, Iwan; Winardi, Bambang (Universitas Diponegoro, 2018)
Grid Side Converter (GSC) is a power converter device that have important role in electrical energy conversion systems especially in the utilization of renewable energy sources in order to be connected to the grid. Based on the grid connection requirements, the GSC should be able to operate even if the grid is experiencing interference. Based on the problem, the GSC control system technically should have ability to detect grid disturbances quickly by using Phase Locked Loop (PLL) method that can provide grid voltage information. Compared with other PLL algorithms, the Second Order Generalized Integrator-Phase Locked Loop (SOGI-PLL) has adaptive-filtering characteristics in adjusting phase information. The SOGI-PLL method in this final project will be implemented for single phase system using dsPIC30F4011 microcontroller with PI controller. PI controller is expected to make the system has a fast response to the changes that occur, because the purpose of the PLL’s own needs is to get the results of grid voltage information such as magnitude, frequency, and phase in realtime. As the results, the SOGI-PLL algorithm through the use of ZMPT101B sensor shows the magnitude, frequency, and phase information is suitable with the grid voltage. The result of phase estimation have also been implemented in the inverter product development project, so that the output voltage inverter is in phase with the grid voltage.